2020
DOI: 10.1016/j.apmr.2019.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Robot-Assisted Arm Training Plus Hand Functional Electrical Stimulation on Recovery After Stroke: A Randomized Clinical Trial

Abstract: The effects of a robot-assisted arm training plus hand functional electrical stimulation on recovery after stroke: a randomized clinical trial,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 38 publications
2
38
0
Order By: Relevance
“…Previous studies have shown that the mechanism of bilateral movement pattern was that the simultaneous movement of the same muscle groups on both sides was beneficial to the activation of similar neural networks in bilateral hemispheres, thereby reducing inter-hemispheric inhibition and improving the functional performance of paralytic hand (Renner et al, 2020). Several studies showed that bilateral training was superior to neurodevelopment treatment and unilateral robot-assisted training in improving upper limb motor function after stroke (Chen et al, 2019;Straudi et al, 2020). Finally, the linkage device of the robotic glove make it easy to realize the repeated movement of the affected hand, which can continuously provide positive feedback to the central nervous system through the peripheral movement and strengthen the neuronal circuit (Mane et al, 2020), thus facilitating the neural remodeling of the brain on the affected side.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the mechanism of bilateral movement pattern was that the simultaneous movement of the same muscle groups on both sides was beneficial to the activation of similar neural networks in bilateral hemispheres, thereby reducing inter-hemispheric inhibition and improving the functional performance of paralytic hand (Renner et al, 2020). Several studies showed that bilateral training was superior to neurodevelopment treatment and unilateral robot-assisted training in improving upper limb motor function after stroke (Chen et al, 2019;Straudi et al, 2020). Finally, the linkage device of the robotic glove make it easy to realize the repeated movement of the affected hand, which can continuously provide positive feedback to the central nervous system through the peripheral movement and strengthen the neuronal circuit (Mane et al, 2020), thus facilitating the neural remodeling of the brain on the affected side.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we framed the BCI intervention within a long-dose protocol containing treatment components targeting an array of impairments, and proven to have been efficacious upper limb motor function in past work [ 5 6 ]. Specifically, we interleaved clinically-based motor training sessions with the rt-fMRI and the rt-fNIRS; these clinically-based motor training sessions included exercise and standard-practice functional electrical stimulation (FES), both supported by research findings [ 6 , 29 , 30 ]. Thus, the secondary objective was to incorporate the sequential rt-fMRI, rt-fNIRS neural feedback system into a motor learning protocol.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to BWSTT and robotic locomotor therapy, FES and arm/hand robots work to enable greater practice and have shown to be helpful in persons with CNS injuries. 5 , 25 , 62 Pilot testing using robotic glove therapies have been encouraging for improving hand function and pinch grip strength, 25 and in stroke patients there is considerable research being done on robotic assisted arm and hand therapy. 63 A recent randomized controlled trial reported that greater improvements were observed with high intensity hand therapy when controlled for stroke severity.…”
Section: Arm/hand Functionmentioning
confidence: 99%
“… 63 A recent randomized controlled trial reported that greater improvements were observed with high intensity hand therapy when controlled for stroke severity. 62 Thus research on comparative effectiveness of high intensity hand therapy and robotic and/or FES assisted arm/hand therapy should carefully control for degree of myelopathic severity.…”
Section: Arm/hand Functionmentioning
confidence: 99%